Answer:
3x² * (6x² + 4x - 8) = 18x⁴ + 12x³ - 24x²
2x * (9x³ + 6x² - 12x) = 18x⁴ + 12x³ - 24x²
x² * (18x² + 12x - 24) = 18x⁴ + 12x³ - 24x²
6x² * (3x² + 2x - 4) = 18x⁴ + 12x³ - 24x²
Step-by-step explanatation:
Let's set unknown variables as y (and y₁, y₂, etc)
Question 1:
y * (6x² + 4x - 8) = 18x⁴ + 12x³ - 24x²
So, divide both sides by (6x² + 4x - 8)
y = 3x²
Question 2:
2x * (9x^y₁ + y₂*x^y₃ - y₄*x) = 18x⁴ + 12x³ - 24x² '
Divide both sides by 2x.
(9x^y₁ + y₂*x^y₃ - y₄*x) = 9x³ + 6x² -12x
y₁ = 3, y₂ = 6, y₃ = 2, y₄ = 12
Question 3:
x^y * (18x² + 12x - 24) = 18x⁴ + 12x³ - 24x²
Divide both sides by (18x² + 12x - 24)
x^y = x²
Question 4:
y₁ * x^y₂ * (3x² + 2x - 4) = 18x⁴ + 12x³ - 24x²
Divide both sides by (3x² + 2x - 4)
y₁ * x^y₂ = 6x²
y₁ = 6, y₂ = 2
I hope this helps! Feel free to ask any questions!